2019
DOI: 10.1007/s12603-019-1174-1
|View full text |Cite
|
Sign up to set email alerts
|

Low Dietary Protein Intakes and Associated Dietary Patterns and Functional Limitations in an Aging Population: A NHANES Analysis

Abstract: Objective To investigate protein intakes across demographic characteristics in relation to dietary patterns and functional outcomes in older adults. Design Observational and cross-sectional study. Setting Non-institutionalized participants from the 2005–2014 National Health and Nutrition Examination Survey. Participants Data from 11,680 adults were categorized into 51–60 years (n= 4,016), 61–70 years (n=3,854), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 54 publications
3
78
4
3
Order By: Relevance
“…Compared to other studies showing evidence for an association between lower protein intake and worse functional status cross-sectionally [10,15], our participants could be more robust, despite the presence of functional limitations. As participation in both presented studies suggested a certain interest in health-related issues, older adults with rather healthy lifestyles and comparatively good resources to deal with losses in physical function are likely to be over-represented.…”
Section: Role Of Functional Statuscontrasting
confidence: 66%
See 1 more Smart Citation
“…Compared to other studies showing evidence for an association between lower protein intake and worse functional status cross-sectionally [10,15], our participants could be more robust, despite the presence of functional limitations. As participation in both presented studies suggested a certain interest in health-related issues, older adults with rather healthy lifestyles and comparatively good resources to deal with losses in physical function are likely to be over-represented.…”
Section: Role Of Functional Statuscontrasting
confidence: 66%
“…Nevertheless, insufficient protein intake is still prevalent, especially in the "oldest-old" and older adults with functional limitations [11][12][13]. A body of literature highlights the interaction between functional status and protein consumption by identifying a poor functional status as both a consequence and a risk factor of low protein intake [10,14,15]. In addition to the amount of consumed protein, the quality of protein seems to be a factor for maintaining muscle health [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…The NHANES protocol includes a multistage stratified sampling from the non-institutionalized population. [10] The purpose of NHANES is to assess health behavior, health status, and nutrition of civilian residents. The NHANES data come from personal interviews, standardized physical examinations, and laboratory tests.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Hal ini sejalan dengan penelitian sebelumnya yang menunjukkan asupan serat sebagian besar lansia tergolong rendah dengan rerata sekitar 8-9,4 gram/hari. 23,32 Kecukupan protein subjek tergolong baik karena subjek cenderung menyukai olahan kacang-kacangan baik untuk sayur, lauk, maupun selingan. Hal ini sejalan dengan penelitian sebelumnya yang menunjukkan sebagian besar lansia memenuhi kebutuhan asupan protein dengan kecukupan sekitar 10,37-11% dari kebutuhan.…”
Section: Pembahasanunclassified